Analisis Keandalan Sistem Proteksi Kebakaran Pada Bangunan Gedung (Studi Kasus : Gedung Rumah Sakit Pratama Kabupaten Maybrat Provinsi Papua Barat Daya - Kaitana, Beatriks; Safari , Athia; Syara, Elfiyusriningsi (CV. Shofanah Media Berkah, 2024)
Fire is a disaster caused by fire and has the potential to occur anywhere, including hospitals. Maybrat General Hospital, as a health facility for the local community, requires special attention to the physical condition and safety systems of the building to protect patients and users. Evaluating building requirements using the Building Fire Safety Inspection Guidelines (Pd-T-11-2005-C) helps ensure that protection systems are functioning properly. The aim of this research is to evaluate system reliability. fire protection. uses a quantitative descriptive approach, with primary and secondary information from observations, interviews and document reviews. The assessment results show a score of 73.23% out of a score of 100%, which is included in the sufficient category according to the weighting (Pd-T-11-2005-C). As a result, maintenance, routine inspections and the provision of active protection system rescue facilities are required.